EFEKTIVITAS PENGGUNAAN KARTU LADIES “LAWAN DISMENOREA” TERHADAP PENGETAHUAN REMAJA PUTRI tentang DISMENOREA - Ria Gustirini (Masker Medika, 2024)
Introduction :During menstruation, the problem experienced by most women is discomfort or severe pain. This is usually called menstrual pain (dysmenorrhea). There are still many women and even teenagers who consider menstrual pain to be normal, they assume it lasts 1-2 days. One effort to address the problem of lack of knowledge about dysmenorrhea is by providing health education through cards. This research aims to determine the effectiveness of using the ladies' card "against dysmenorrhoea" on young women's knowledge about dysmenorrhoea at SMK Muhammadiyah 02 Palembang.Method: this reserah uses a quantitative approach, the method used in this research is quasi-expermiental with a pre-post test one group design type. Results: research based on statistical analysis of the results of the Wilcoxon Signed Rank Test calculation, it was found that the p-value was 0.00 (<0.05), there was an increase in respondents' knowledge after being given health education using the ladies card "against dysmenorrhoea" from an average pretest result of 42.3 increased with an average posttest result of 82.7. Discussion: It is recommended that card media be used to provide easier health education for teenagers because it has the advantage of being an educational type that can be carried easily and an attractive design that is easy to understand, making it easier to absorb knowledge. Keywords: Dismenorea, Ladies' Cards, Knowledge, Young Women